Alain Rabatel, Homo narrans (ENTHYMEMA, 2009)
The notion of «point of view» is fundamental in order to grasp the values and the worldview communicated by a narrative, to understand the different subjectivities that may dialogue in a story. Every narrative is transversally crossed by an implicit argumentation that is made effective and not intrusive thanks to the suitable context provided by the narrative itself. Alain Rabatel uses his competence as a linguist to give precious indications on how discourse properties may be signs of the argumentative strategies operating in a narrative.